Entangled Plumwoods: Stewardship as Grassroots Conservation Humanities - Natasha Fijn (Humanities, 2024)
Hundreds of thousands of hectares of bushland and accompanying biodiversity were lost over a few short weeks during the Black Summer fires of 2019–2020 along the east coast of Australia. On the night of 19 December 2019, fire swept up the escarpment from the coast, slowed down with the thick understory of temperate rainforest and burnt through the lower dry sclerophyll forest on Plumwood Mountain. The aftermath of the bare, burnt landscape meant a significant change in the structure and diversity of vegetation, while the consequences of the fire also brought about fundamental changes to Plumwood as a conservation and heritage organisation. Plumwood Mountain as a place, the individual plumwood tree as an agentive being, Val Plumwood as a person and Plumwood as an organisation are all an entangled form of natureculture and indicative of a practice-based conservation humanities approach. Conservation as part of the environmental humanities can offer an alternative to mainstream models of conservation with the potential to instigate active participation on the ground, engaging in a different form of stewardship.